Modulation of post hatch-growth and immunocompetence through in ovo injection of limiting amino acids in broiler chickens - Bhanja, Subrat K; Mandal, Asit Baran; Agarwal, Sushil K; Majumdar, Samir (The Indian Journal of Animal Sciences, 2012)
Early post-hatch growth and immunity was assessed through in ovo injection of some critical amino acids on 14th d of incubation at the broad end of the egg using 25 mm needle. Percent hatchability in lysine (lys) and arginine (arg) injected groups were better than un-injected control group. Threonine (thr) and methionine (met) injected eggs had higher chick weight and chick to egg weight ratio and met and arg injected chicks had higher fourth and seventh week body weight than un–injected control chicks. No significant difference was recorded for FCR of in ovo amino acids injected birds. Met and glycine (gly) injected chicks had higher bursa weight, whereas, those injected with met thr, gly and isoleucine (ile) had higher spleen weight on the day of hatch. Humoral immune response (SRBC titre) was higher in most of the amino acid injected chicks except lys group. Cell mediated immunity (response to PHAP mitogen) was higher in lys, arg, gly and ile injected chicks. The chicks injected with amino acids invariably had higher plasma protein and lower plasma glucose on the day of hatch. It may be concluded that met and thr were critical for the growth of chicken embryo, however, during post–hatch period met and arg played major role. In ovo injected amino acids can also act as immunomodulator but their role in gastrointestinal development needs further research.